2003
DOI: 10.1161/01.cir.0000045668.71683.92
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Interacts With Cytomegalovirus Seropositivity and High C-Reactive Protein in Reducing Mortality Among Patients With Angiographically Significant Coronary Disease

Abstract: Background-Seropositivity to cytomegalovirus (CMV) and elevated C-reactive protein (CRP) may jointly predict increased mortality rates in patients with coronary artery disease (CAD). Therapy with statins reduces lipid levels but may also have other beneficial (eg, antiinflammatory) effects. This study prospectively evaluated the effect of statins on CMV-and CRP-associated death among patients with significant, angiographically defined CAD. Methods and Results-We monitored 2315 patients with angiographically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…5,8 Nor did we include exclusively elderly patients or only those with coronary artery disease, as in other studies. 3,4,5,13,18 Our observations appear to support previous studies and contradict others. Three recent studies did observe an association between those with high antibody titers to CMV and reduced longevity.…”
Section: Discussionsupporting
confidence: 64%
“…5,8 Nor did we include exclusively elderly patients or only those with coronary artery disease, as in other studies. 3,4,5,13,18 Our observations appear to support previous studies and contradict others. Three recent studies did observe an association between those with high antibody titers to CMV and reduced longevity.…”
Section: Discussionsupporting
confidence: 64%
“…These results, while confirming the anti-inflammatory properties of statins, identify novel pharmacological targets potentially relevant in improving the therapeutic profile of statins in the treatment of atherosclerosis progression and, possibly, CMV infection development. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Long-term statin administration in ambulatory patient populations has been previously associated with a reduced risk of adverse cardiovascular events, including death, MI, stroke, and renal dysfunction. [1][2][3][4][5][6][7][8][9][10] Furthermore, the beneficial effects of statin therapy are not limited to patients with hypercholesterolemia. Multiple randomized clinical trials have shown that even in patients with normal total and low-density lipoprotein cholesterol levels, long-term statin administration is associated with reduced incidence of adverse cardiovascular outcomes and a decreased need for coronary angioplasty or CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] However, the beneficial effects of statin therapy on adverse cardiovascular events in the acute perioperative period are largely unknown. [11][12][13] Recently, statins were shown to be associated with a reduced incidence of perioperative mortality in patients undergoing major noncardiac vascular surgery.…”
mentioning
confidence: 99%